Otimização no corte de tubos estruturais: aplicação na indústria aeronáutica agrícola - Abuabara, Alexander (2006)
The Cutting Stock Problem consists of determining the best form to cut units of material (objects in supply), producing a set of lesser units (demanded item), with speciﬁc dimensions, that are ordered through an order wallet. To minimize the loss of material this study described a method of evaluation and optimization of the process planning of the cutting of metallic structural tubes used in the manufacturing of small aircrafts for the agricultural aeronautic industry. In order, to support the decisions in the cutting process it was developed an optimization approach based on mathematical mixed integer programming models. The mathematic models are resolved in GAMS/CPLEX, using the production data of Neiva, an aeronautical company subsidiary of Embraer. The results showed that it is possible obtain signiﬁcant proﬁts in the production in with the application of mathematical models in the process of cut in the aeronautic industry. Mathematical models have a potential to generate beneﬁcial solutions in the production process reducing the costs of production with the re-use of the leftovers.